2018
DOI: 10.1111/hae.13494
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia gene therapy: From trailblazer to gamechanger

Abstract: Haemophilia is an attractive disease target for gene therapy that fostered the development of the field at large. The delivery of the clotting factor genes into the patients' cells could be accomplished using different types of gene delivery vehicles or vectors. Adeno-associated viral vectors (AAV) and lentiviral vectors represent some of the most promising gene delivery technologies that allow for a relatively efficient delivery of the therapeutic FVIII and FIX transgenes into the relevant target cells. To re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 128 publications
(280 reference statements)
0
12
0
Order By: Relevance
“…Adeno-associated viruses (AAVs) are increasingly utilized as delivery vehicles due to their strong clinical safety record, low pathogenicity, and stable, non-integrating expression in vivo 1 . AAVs were first approved for gene therapy in humans in 2012 to treat lipoprotein lipase deficiency 2 , and have more recently been approved to treat spinal muscular atrophy 3 , retinal dystrophy and hemophilia 4,5 . Many more advanced-stage clinical trials using AAVs are underway [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Adeno-associated viruses (AAVs) are increasingly utilized as delivery vehicles due to their strong clinical safety record, low pathogenicity, and stable, non-integrating expression in vivo 1 . AAVs were first approved for gene therapy in humans in 2012 to treat lipoprotein lipase deficiency 2 , and have more recently been approved to treat spinal muscular atrophy 3 , retinal dystrophy and hemophilia 4,5 . Many more advanced-stage clinical trials using AAVs are underway [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Some of these products may be administered subcutaneously and no longer require intravenous injections. However, new treatments may have drawbacks of their own, including known and unknown risks, as summarised in Table 1 [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Overview of haemophilia A and B treatment products currently under development or marketed recently, with their benefits, potential disadvantages and mechanisms of action[10][11][12][13][14] …”
mentioning
confidence: 99%
“…1 Here, we describe 2-year and 3-year safety and efficacy data after the administration of AAV5-hFVIII-SQ (valoctocogene roxaparvovec) in men with severe hemophilia A. In addition to providing clinical safety and efficacy data, this research contributes to a mechanistic understanding of the variability observed in gene therapy studies, [2][3][4][5][6] thus providing insights into mechanisms of DNA persistence and durable expression.…”
mentioning
confidence: 99%